Impact of Photoactivated Disinfection on Dentin Permeability and Bacterial Eradication - Ashtha Arya; Jasmine Marwaha; Divya Batra; Ashutosh Yadav; Manish Bhargava; Ataul Hafeez Imran (Journal of Pharmacy and Bioallied Sciences)
Background: The increasing prevalence of antibiotic resistance has necessitated the exploration of alternative antimicrobial approaches in dentistry. Photoactivated disinfection (PAD) has gained attention for its potential to reduce bacterial load and enhance dentin permeability in endodontic treatments. This study evaluates the impact of PAD on dentin permeability and its efficacy in eradicating bacterial pathogens. Materials and Methods: A total of 40 extracted human premolars were selected and standardized for this in vitro study. Dentin disks were prepared and divided into four groups: Group A (control, no treatment), Group B (irrigation with NaOCl), Group C (PAD using methylene blue), and Group D (PAD using toluidine blue). Each group underwent permeability assessment using fluid filtration techniques. The bacterial eradication efficiency was tested by inoculating Enterococcus faecalis into dentinal tubules and quantifying colony-forming units (CFUs) before and after treatment. Arbitrary permeability values and CFU counts were recorded for statistical comparison. Results: Group C (PAD with methylene blue) showed a significant increase in dentin permeability (25 ± 5 units) compared with the control (10 ± 3 units, P < 0.05). Group D demonstrated superior bacterial eradication (95% reduction in CFUs) compared with Group B (80% reduction) and Group A (20% reduction, P < 0.01). The combination of PAD and photosensitizers exhibited enhanced antimicrobial effects and improved dentin permeability. Conclusion: PAD is an effective adjunctive technique in endodontics, significantly improving dentin permeability and demonstrating superior bacterial eradication compared with conventional irrigation alone. These findings suggest that incorporating PAD could optimize clinical outcomes in root canal disinfection.